Validation of Farmer Perceived Soil Fertility Improving Tree Species in Agropastoral Communities of Bushenyi District - Albert. K. Muzoora; Nelson Turyahabwe; Jackson G. M. Majaliwa (International Journal of Agronomy)
In sub-Saharan Africa, including Uganda, there is declining soil fertility and limited on-farm use of inorganic fertilizers due to poverty and limited subsidies for inorganic fertilizer use. Thus, integration of soil fertility improving tree species (SFITs) in farming systems remains a plausible option to sustaining soil productivity. However, knowledge of the effects of many of the locally growing farmer perceived soil fertility enhancing tree species on to soil chemical and nutrient contents are thus still lacking, and this has constrained decisions on their adoption and scaling up. The objectives of this paper were to identify farmers' preferred soil fertility improving tree species in agropastoral communities of Kyeizooba subcounty Bushenyi district, and characterize their litter content and assess their effect on selected soil chemical properties. Semistructured questionnaires were administered to 333 randomly selected agropastoral farmers. Litter and soils under canopy soils were sampled from three different environments: Under canopy radius (A), canopy edge (B), open pasture land up to thrice the canopy radius (C). Results revealed Eucalyptus as the most common tree species on livestock farms, followed by Erythrina abyssinica. The highest litter content was recorded for Markhamia lutea (240 g/cm2 under its canopy) followed by Croton macrostachyus (90 g/cm2), and 19 g/cm2 Erythrina abyssinica. Nitrogen was higher (P=.02) in Erythrina abyssinica litter, K and carbon in Croton macrostachyus litter (P=.03). These results give evidence that of soil improvers Erythrina abyssinica, Croton macrostachyus, and Markhamia lutea may positively affect soil fertility. Farmers' indigenous knowledge and or valuation of important tree species can be relied on, and thus, their indigenous knowledge need to be incorporated during identification of tree species for promotion in farming systems.